The peripheral other and the construction of new social relations in Andrea Levy's Small Island - (:unkn) unknown (My University, 2023)
Andrea Levy begins her story in Small Island (2004) with a prologue that speaks of the gathering of colonial subjects at the 1924 British Empire Exhibition. Although the colonial subjects are portrayed as uncivilized and as the peripheral Other, the Exhibition sets the stage for alterity in social relations and in the rewriting of history that renders the former members of British colonies invisible through an encounter between an African man and young Queenie, portrayed as the archetypal figure of England, the Mother Country. By offering to shake hands with Queenie rather than be spoken about, the African man not only changes Queenie’s perception about Africa but also speaks himself into subjectivity. The quest to reposition oneself becomes a leitmotif in the narrative as events and human contacts offer new perspectives for both Black and White people to reconstruct their identities. Significant is the fact that Black women are in the forefront of this reverse colonization as they take up the responsibility of nurturing a new British multicultural society and fostering new social relations as Hortense does in the novel. Hortense’s ability to reposition herself socially and historically paves the way for her to construct what I have termed a “rhizomatic womb-space”—a social, creative, ideological, and biological space through which women conceive, nurture, and offer new social relations built not on the either/or dichotomy that gender, class, race, and nationality evoke, but on fluid identity formations and social relations. She not only becomes the voice that opens and ends this important narrative but also is the lone voice that speaks of the birth and nurturing of a new British multicultural society. The history rewritten through the birth of Queenie’s biracial child is one of conquest, resilience, resistance, love, inclusion, and emplacement. It is one made possible through the restructuring of sociohistorical narratives and repositioni
Keywords: African Research